Enhancement in brain uptake of vitamin D3 nanoemulsion for treatment of cerebral ischemia: formulation, gamma scintigraphy and efficacy study in transient middle cerebral artery occlusion rat models. (2nd October 2020) - Kumar, Mukesh; Nishad, Dhruv Kumar; Kumar, Anoop; Bhatnagar, Aseem; Karwasra, Ritu; Khanna, Kushagra; S, Keerthana; Sharma, Deeksha; Dua, Kamal; Mudaliyar, Vijaybabu; Sharma, Nitin
Abstract: Aim: For the treatment of cerebral ischaemia, vitamin-D3 loaded nanoemulsions were developed. Method: Tween 20 and polyethylene glycol were chosen as surfactant/co-surfactant, while oleic acid as the oil phase. The formulation was characterised for various in-vitro parameters. Targeting efficiency was investigated through radiometry, gamma scintigraphy and efficacy was studied in transient middle cerebral artery occlusion (MCAo) rat model. Result: Vitamin D3 -nanoemulsion showed a mean size range of 49.29 ± 10.28 nm with polydispersity index 0.17 ± 0.04 and zeta potential 13.77 mV. The formulation was found stable during thermodynamic stability study and permeated within 180 min through sheep nasal mucosa (permeation coefficient 7.873 ± 0.884 cm/h). Gamma scintigraphy and radiometry assay confirmed better percentage deposition (2.53 ± 0.17%) of 99m Tc-vitamin D3 -nanoemulsion through nasal route compared to IV administered 99m Tc-vitamin D3 solution (0.79 ± 0.03%). Magnetic Resonance Imaging (MRI) of the ischaemic model confirmed better efficacy of vitamin D3 -nanoemulsion. Conclusion: This work demonstrated better permeation, deposition, and efficacy of vitaminD3 -nanoemulsion through the intranasal route.